AZYMUTH - 40 years at the forefront of Brazilian jazz - Rodrigues, André (2012)
This article aims to discuss the longevity and the innovations of one of the most important in Brazilian instrumental groups, the trio Azimuth. The study provides an overview of all their work, and presents through-time contextual analysis of some of their most significant albums. It also examines the mixture of samba and jazz, explores some of the reasons for Azymuth's rich and long-productivity and also presents some of the technical innovations that they brought to the music - and to the musicians, changing the panorama of Brazilian instrumental music. The approach was to listening to these albums and discussing their work, mixing the author's personal impressions and analysis with a short research of the group's history and output. The authors, of course, have been long time admirers of the Azymuth's music. The paper aims to bring Azymuth's music to a discussion in the academic environment based on the belief that their music to be relevant and cutting edge in the Brazilian music history.